An Exploratory Study of Group Development and Team Learning. (3rd March 2015) - Raes, Elisabeth; Kyndt, Eva; Decuyper, Stefan; Van den Bossche, Piet; Dochy, Filip
<x xml:space="preserve">Abstract</x> Teams need to pass through a series of development stages before they can operate effectively, and, in a changing context, it has also been demonstrated that teams need to continue learning in order to remain effective. This article aims to explore the relationship between team development and team learning. In particular, it focuses on when and why basic team learning processes such as sharing information, co‐construction, and constructive conflict occur during different phases of development. It can be hypothesized that although each stage of team development is characterized by specific learning tasks, team learning processes occur more in certain stages than in others. The results from a model‐based cluster analysis and ANOVA analyses on a sample of 44 professional teams show that team learning occurs more in the later phases of group development due to higher levels of team psychological safety and group potency.